Genital and Intertriginous Rashes Refractory to Antimicrobial Treatments: Have You Thought about Crohn's Disease?. (23rd July 2021) - O'Farrell, Candelaria; Roberts, Annette; Riera Canales, Claudia; Firestone Baum, Carrie; Felipez, Lina Maria
Abstract : Crohn's disease is an inflammatory bowel disease that can have multiple extraintestinal manifestations and can develop prior to, following, or simultaneously with gastrointestinal tract involvement (Aberumand et al. (2017), Georgious et al. (2006), Larsen et al. (2010), Levine and Burakoff (2011), Louis et al. (2018)). This report examines the case of a 16-year-old male with a rash of the genital, intergluteal, and inguinal regions refractory to antimicrobial treatments suspicious for an extraintestinal manifestation of Crohn's disease. The patient was diagnosed with inflammatory, nonfistulizing colonic Crohn's disease following presentation with gastrointestinal symptoms including abdominal pain and bloody stools 6 months after the onset of the rash. The genital lesions resolved after starting treatment for Crohn's disease with adalimumab.